Search
Ask a question
0

How do I simplify...

y -5  = 3 -  1 - 2y
y+4            y + 4

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Carol H. | Experienced Mathematics Tutor w/ Master's Degree in MathExperienced Mathematics Tutor w/ Master'...
4.9 4.9 (263 lesson ratings) (263)
0
y - 5 = 3(y + 4) - 1 - 2y
y + 4     (y + 4)      y + 4
 
y - 5 = 3y + 12 - 1 + 2y      multiplying both sides by (y + 4) eliminates that binomial
 y + 4          y + 4
 
y - 5 =   5y + 11
-5y   = -5y
-4y - 5 =  11
      + 5 = +5
-4y      = 16
 -4          -4
 
      y = -4